2005
DOI: 10.1007/s10067-005-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

Early assessment of rapidly progressive interstitial pneumonia associated with amyopathic dermatomyositis

Abstract: Amyopathic dermatomyositis (ADM) is occasionally complicated by rapidly progressive interstitial pneumonia (RPIP), and in such cases, diffuse alveolar damage (DAD) is usually diagnosed at autopsy. Here, we present three patients with RPIP accompanied by ADM in whom lung disease was assessed at an early stage. High-resolution computed tomography (HRCT) carried out before the onset of dyspnoea revealed uniformly subpleural reticular opacity with faint ground-glass attenuation. At that stage, surgical lung biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 18 publications
3
43
1
3
Order By: Relevance
“…Regarding the anti-Jo-1 antibody, only one patient with chronic ILD-ADM had this antibody among the present ILD-ADM study. To date, several studies have reported a low incidence of anti-Jo-1 antibody in ILD-ADM patients [11][12][13][17][18][19]. The current results were consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the anti-Jo-1 antibody, only one patient with chronic ILD-ADM had this antibody among the present ILD-ADM study. To date, several studies have reported a low incidence of anti-Jo-1 antibody in ILD-ADM patients [11][12][13][17][18][19]. The current results were consistent with those studies.…”
Section: Discussionsupporting
confidence: 92%
“…As ADM is a rare disease, previous studies of ILD-ADM included only one, or a few patients [7][8][9][10][11][12][13]. The present study investigated the highest number of patients with ILD-ADM so far.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations